Fabrication of Trifunctional Polyoxometalate‐Decorated Chitosan Nanofibers for Selective Production of 2, 5‐Diformylfuran. Issue 15 (15th July 2019) - Li, Yiming; Li, Peili; Cao, Ping; Li, Ying; Wang, Xiaohong; Wang, Shengtian
Abstract: Trifunctional catalysts based on polyoxometalate (POM) decorating chitosan nanofibers (H5 PMo10 V2 O40 /chitosan nanofibers, abbreviated as HPMoV/CS‐f), synthesized by using the electrospinning method, realized highly efficient oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐diformylfuran (DFF). Decorating chitosan nanofibers with POMs generated enhanced catalytic activity by merging their unique individual properties of redox ability, Brønsted acidity, basicity, and nanofiber structure with higher surface area. As a result, HPMoV/CS‐f(25) (with 25 representing the POM amount) was found to be the most active catalyst in the aerobic oxidation of HMF, resulting in 94.1 % DFF yield at 96.2 % conversion in DMSO at 120 °C for 6 h, whereas 56.2 % DFF yield at 95.0 % conversion was obtained in water at 140 °C for 8 h. Importantly, DFF could be produced in one pot in one step to give 61.9 and 31.4 % yield, respectively, directly from fructose and glucose under the reaction conditions of 140 °C, 6 h in DMSO, which was owing to the suitable balance of Brønsted acidity and basicity of the trifunctional HPMoV/CS‐f(25). Moreover, HPMoV/CS‐f showed good stability and ability to be reused at least ten times without leaching of the POMs from the chitosan nanofibers. Abstract : Trifunctional catalysts based on H5 PMo10 V2 O40 polyoxometalate (POM) decorating chitosan nanofibers (HPMoV/CS‐f) are synthesized through electrospinning, resulting in highly efficient oxidation of 5‐hydroxymethylfurfural (HMF) to 2, 5‐diformylfuran (DFF).